Naturalistic fMRI Mapping Reveals Superior Temporal Sulcus as the Hub for the Distributed Brain Network for Social Perception - Lahnakoski, Juha M.; Glerean, Enrico; Salmi, Juha; Jääskeläinen, Iiro P.; Sams, Mikko; Hari, Riitta; Nummenmaa, Lauri (Frontiers in Human Neuroscience, 2012)
Despite the abundant data on brain networks processing static social signals, such as pictures of faces, the neural systems supporting social perception in naturalistic conditions are still poorly understood. Here we delineated brain networks subserving social perception under naturalistic conditions in 19 healthy humans who watched, during 3-tesla functional magnetic imaging (fMRI), a set of 137 short ( 16 s each, total 27 min) audiovisual movie clips depicting pre-selected social signals. Two independent raters estimated how well each clip represented eight social features (faces, human bodies, biological motion, goal-oriented actions, emotion, social interaction, pain, and speech) and six filler features (places, objects, rigid motion, people not in social interaction, non-goal-oriented action and non-human sounds) lacking social content. These ratings were used as predictors in the fMRI analysis. The posterior superior temporal sulcus (STS) responded to all social features but not to any non-social features, and the anterior STS responded to all social features except bodies and biological motion. We also found four partially segregated, extended networks for processing of specific social signals: 1) a fronto-temporal network responding to multiple social categories, 2) a fronto-parietal network preferentially activated to bodies, motion and pain, 3) a temporo-amygdalar network responding to faces, social interaction and speech, and 4) a fronto-insular network responding to pain, emotions, social interactions, and speech. Our results highlight the role of the posterior STS in processing multiple aspects of social information, as well as the feasibility and efficiency of fMRI mapping under conditions that resemble the complexity of real life.